Concrete anti-cracking material as well as preparation method and application thereof
By immersing activated carbon in an aqueous solution of cement hydration temperature rise inhibiting material and spraying paraffin on its surface, concrete crack-resistant materials are formed, which solves the problem that concrete is prone to cracks in large-scale projects, and the effect of reducing hydration heat and improving crack resistance is achieved.
Patent Information
- Application Number
- CN202510099008.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Concrete is prone to cracks in large-scale projects, which leads to accelerate invasion of water and harmful substances and reduces the durability and service life of the project.
By immersing the activated carbon in an aqueous solution of the cement hydration temperature rise inhibiting material, modified activated carbon is obtained and paraffin is sprayed on the surface to form a concrete crack-resistant material. This material suppresses the synergistic effect of the material through the hydration temperature rise of paraffin and cement, reduces the heat of hydration, and reduces the occurrence of temperature deformation cracks.
It effectively reduces the temperature deformation cracks caused by the large temperature difference between the inside and outside concrete, and improves the crack resistance of concrete.
Smart Images

Figure BDA0005253674850000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a concrete anti-cracking material and a preparation method and application thereof. Background Art
[0002] With the continuous improvement of social living standards and scientific and technological levels, people have put forward higher requirements on many aspects of buildings, such as structural types, safety performance and cost-effectiveness. Especially in special engineering fields such as large-span, high-rise buildings, marine engineering, military industry, etc., the quality requirements for building materials such as concrete are more stringent.
[0003] The problem of concrete cracks is a major issue that the civil engineering field has to face, especially in today's large-scale engineering fields. Although the appearance of concrete cracks will not cause significant damage to the overall structural strength in a short period of time, the presence of cracks will accelerate the intrusion of water and harmful substances, reducing the durability and long-term service life of the overall project.
[0004] Therefore, it is necessary to provide a concrete anti-cracking material. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a concrete anti-cracking material and a preparation method and application thereof.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is a method for preparing a concrete anti-cracking material, comprising the following steps:
[0008] The activated carbon is impregnated in an aqueous solution of a cement hydration temperature rise suppression material, and after the impregnation is completed, the impregnated activated carbon is collected and dried to obtain modified activated carbon;
[0009] After the paraffin is dissolved, it is sprayed on the surface of the modified activated carbon and dried to obtain the concrete anti-cracking material.
[0010] The second technical solution of the present invention is a concrete anti-cracking material prepared by the above preparation method.
[0011] A third technical solution of the present invention is an application of the above concrete anti-cracking material in the preparation of crack-resistant concrete.
[0012] A fourth technical solution of the present invention is a crack-resistant concrete, the raw materials of which include the above-mentioned concrete crack-resistant material.
[0013] The present invention discloses the following technical effects:
[0014] The concrete anti-cracking material provided by the present invention suppresses hydration heat through the dual effects of paraffin wax and cement hydration temperature rise suppression material, thereby reducing temperature deformation cracks caused by tensile stress exceeding the limit due to a large temperature difference between the inside and outside of the concrete.
[0015] When the concrete anti-cracking material provided by the present invention is used to prepare anti-cracking concrete, the anti-cracking performance of the concrete is improved through the synergistic reinforcement effect of the concrete anti-cracking material and carbon fiber. DETAILED DESCRIPTION
[0016] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0017] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0018] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0019] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0020] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0021] A first aspect of the present invention provides a method for preparing a concrete anti-cracking material, comprising the following steps:
[0022] The activated carbon is impregnated in an aqueous solution of a cement hydration temperature rise suppression material, and after the impregnation is completed, the impregnated activated carbon is collected and dried to obtain modified activated carbon;
[0023] After the paraffin is dissolved, it is sprayed on the surface of the modified activated carbon and dried to obtain the concrete anti-cracking material.
[0024] In some embodiments of the present invention, the cement hydration temperature rise suppression material is selected from at least one of boric acid, citric acid, malic acid, tartaric acid and salicylic acid.
[0025] In some embodiments of the present invention, the mass ratio of the activated carbon, the cement hydration temperature rise suppression material, and the paraffin is 5:(2-8):(3-10).
[0026] In the present invention, the amount of water used to dissolve the cement hydration temperature rise suppression material is not particularly limited, as long as the amount of water used to dissolve the cement hydration temperature rise suppression material sufficiently and to completely impregnate the activated carbon is sufficient.
[0027] The present invention does not make any special requirements for the drying method, and a technical solution well known to those skilled in the art can be selected, such as air drying at room temperature.
[0028] The second aspect of the present invention provides a concrete anti-cracking material prepared by the above preparation method.
[0029] A third aspect of the present invention provides a use of the above concrete anti-cracking material in preparing anti-cracking concrete.
[0030] A fourth aspect of the present invention provides a crack-resistant concrete, the raw materials of which include the above-mentioned concrete crack-resistant material.
[0031] In some embodiments of the present invention, the anti-cracking concrete raw materials include the following components in parts by mass: 200-300 parts of silicate cement, 35-50 parts of fly ash, 15-20 parts of concrete anti-cracking materials, 180-250 parts of coarse aggregate, 100-150 parts of fine aggregate, 25-40 parts of carbon fiber, 1-10 parts of water reducer and 80-120 parts of water.
[0032] In some embodiments of the present invention, the silicate cement is P.O42.5 ordinary silicate cement; the fly ash is primary fly ash or secondary fly ash.
[0033] In some embodiments of the present invention, the coarse aggregate is crushed stone; the particle size of the coarse aggregate is 5-20 mm and is continuously assembled; the fine aggregate is river sand; the particle size of the fine aggregate is 1-3 mm.
[0034] In some embodiments of the present invention, the aspect ratio of the carbon fiber is 13-18:1.
[0035] In some embodiments of the present invention, the water reducer is a polycarboxylate water reducer, and the water reduction rate is ≥20%.
[0036] At present, the two main methods to solve the temperature deformation cracks caused by tensile stress exceeding the limit due to the large temperature difference between the inside and outside of concrete are to lay cooling water pipes and add hydration heat inhibition materials that can regulate the cement hydration rate. Directly laying cooling water pipes requires a large amount of work and will affect the strength of cement in the later stage. Directly adding hydration heat inhibition materials can make the concrete have better hydration heat inhibition in the initial stage, but the duration is short. The above methods cannot effectively reduce the hydration heat of concrete, thus leading to the generation of temperature deformation cracks. The concrete anti-cracking material provided by the present invention is a paraffin phase change microsphere wrapped with a cement hydration temperature rise inhibitory material. When the concrete is hydrated, as the temperature rises, the paraffin dissolves, and the cement hydration temperature rise inhibitory material inside is released to reduce the hydration heat. At the same time, the melting of the paraffin will also absorb a part of the hydration heat, further reducing the hydration heat reaction. When the subsequent temperature is reduced, the paraffin solidifies and wraps the unreleased cement hydration temperature rise inhibitory material. When the temperature rises next time, the process of paraffin dissolution-cement hydration temperature rise inhibitory material release is repeated, and the hydration heat of cement is reduced by the synergistic effect of paraffin and cement hydration temperature rise inhibitory material. At the same time, combined with the reinforcing effect of fiber, the crack resistance of concrete is jointly improved.
[0037] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0038] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0039] In the embodiment, the silicate cement is P.O42.5 ordinary silicate cement, the fly ash is secondary fly ash, the coarse aggregate is continuously assembled crushed stone with a particle size of 5-20 mm, the fine aggregate is river sand with a particle size of 1-3 mm, the aspect ratio of the carbon fiber is 13-18:1, the water reducer is a polycarboxylic acid water reducer, and the water reduction rate is ≥20%.
[0040] Example 1
[0041] This embodiment provides a concrete anti-cracking material, and the preparation steps are as follows:
[0042] After dissolving 7 parts of citric acid in water, 5 parts of activated carbon were immersed in the citric acid aqueous solution for 30 minutes, and then filtered to collect the immersed activated carbon and dry it to obtain modified activated carbon;
[0043] After dissolving 10 parts of paraffin wax, spray it on the surface of the modified activated carbon. While spraying, shake the modified activated carbon to ensure that the paraffin wax can evenly adhere to the surface of the modified activated carbon. Dry it to obtain a concrete anti-cracking material.
[0044] Example 2
[0045] The present embodiment provides a crack-resistant concrete, the raw materials of which are the following components in parts by mass: 200 parts of silicate cement, 35 parts of fly ash, 15 parts of the concrete crack-resistant material of Example 1, 180 parts of coarse aggregate, 100 parts of fine aggregate, 25 parts of carbon fiber, 3 parts of water reducer and 113 parts of water.
[0046] The preparation method of crack-resistant concrete is:
[0047] Step 1. Mix silicate cement, fly ash, concrete anti-cracking material, coarse aggregate, fine aggregate, carbon fiber and water reducing agent evenly, add water, and stir for 30 minutes to obtain cement slurry;
[0048] Step 2. Pour the cement slurry into the mold, vibrate and compact it, and demould it after curing for 28 days. The curing temperature is 20-25℃ and the humidity is ≥95%.
[0049] Example 3
[0050] The present embodiment provides a crack-resistant concrete, the raw materials of which are the following components in parts by mass: 235 parts of silicate cement, 42 parts of fly ash, 17 parts of the concrete crack-resistant material of Example 1, 193 parts of coarse aggregate, 138 parts of fine aggregate, 30 parts of carbon fiber, 2 parts of water reducer and 120 parts of water.
[0051] The preparation method of crack-resistant concrete is the same as that of Example 2.
[0052] Example 4
[0053] The present embodiment provides a crack-resistant concrete, the raw materials of which are the following components in parts by mass: 295 parts of silicate cement, 48 parts of fly ash, 20 parts of the concrete crack-resistant material of Example 1, 247 parts of coarse aggregate, 143 parts of fine aggregate, 33 parts of carbon fiber, 3.5 parts of water reducer and 120 parts of water.
[0054] The preparation method of crack-resistant concrete is the same as that of Example 2.
[0055] Comparative Example 1
[0056] The only difference from Example 4 is that the addition of concrete anti-cracking material is omitted, and the remaining steps and parameters are the same as those of Example 4.
[0057] Comparative Example 2
[0058] The only difference from Example 4 is that 20 parts of concrete anti-cracking material are replaced by 20 parts of citric acid, and the remaining steps and parameters are the same as those of Example 4.
[0059] Comparative Example 3
[0060] The preparation method of the paraffin microspheres in this comparative example is the same as the preparation method of the concrete anti-cracking material in Example 1, the only difference being that the addition of citric acid is omitted.
[0061] The raw materials of the crack-resistant concrete in this comparative example are the following components by mass: 295 parts of silicate cement, 48 parts of fly ash, 20 parts of paraffin microspheres, 247 parts of coarse aggregate, 143 parts of fine aggregate, 33 parts of carbon fiber, 3.5 parts of water reducer and 120 parts of water. (The difference from Example 4 is that the concrete crack-resistant material is replaced by paraffin microspheres)
[0062] The preparation method of crack-resistant concrete is the same as that of Example 2.
[0063] Effect verification:
[0064] (1) The crack-resistant concrete of Examples 2-4 and Comparative Examples 1-3 was tested. The compressive strength was measured according to the test method specified in (GB / T50081-2019), the 28d shrinkage was measured according to the test method specified in JC / T 2381-2016, and the creep stress was measured according to the method specified in T0578-2020. The specific measurement results are shown in Table 1.
[0065] (2)) Cracking performance test: Prepare crack-resistant concrete specimens according to GB / T50081-2002 Standard Specification for Test Methods of Mechanical Properties of Ordinary Concrete, prepare a 600mm×400mm×100mm flat test mold, and use a curved wavy stress constraint strip to provide constraints. Apply concrete to the test mold, vibrate for 1 minute, smooth the surface, and move it into the observation room. The temperature in the observation room is 24-26℃ and the relative humidity is 60%-70%. After the test mold is placed, use an electric fan to blow the surface at a wind speed of 8m / s for 24 hours. During this period, observe and evaluate the crack resistance level. The specific test results are shown in Table 1.
[0066] Table 1 Experimental data of different embodiments and comparative examples
[0067]
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a concrete anti-cracking material, characterized in that: The following steps are involved: The activated carbon is impregnated in an aqueous solution of a cement hydration temperature rise suppression material, and after the impregnation is completed, the impregnated activated carbon is collected and dried to obtain modified activated carbon; After the paraffin is dissolved, it is sprayed on the surface of the modified activated carbon and dried to obtain the concrete anti-cracking material.
2. The method for preparing the concrete anti-cracking material according to claim 1, characterized in that: The cement hydration temperature rise suppression material is selected from at least one of boric acid, citric acid, malic acid, tartaric acid and salicylic acid.
3. The method for preparing the concrete anti-cracking material according to claim 1, characterized in that: The mass ratio of the activated carbon, the cement hydration temperature rise suppression material and the paraffin is 5:(2-8):(3-10).
4. A concrete anti-cracking material prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the concrete anti-cracking material according to claim 4 in preparing anti-cracking concrete.
6. A crack-resistant concrete, characterized in that: The raw materials include the concrete anti-cracking material according to claim 4.
7. The crack-resistant concrete according to claim 6, characterized in that: The raw materials include the following components in parts by mass: 200-300 parts of silicate cement, 35-50 parts of fly ash, 15-20 parts of the concrete anti-cracking material according to claim 4, 180-250 parts of coarse aggregate, 100-150 parts of fine aggregate, 25-40 parts of carbon fiber, 1-10 parts of water reducer and 80-120 parts of water.
8. The crack-resistant concrete according to claim 7, characterized in that: The silicate cement is P.O42.5 ordinary silicate cement; the fly ash is primary fly ash or secondary fly ash.
9. The crack-resistant concrete according to claim 7, characterized in that: The coarse aggregate is crushed stone; the particle size of the coarse aggregate is 5-20 mm and is continuously assembled; the fine aggregate is river sand; the particle size of the fine aggregate is 1-3 mm.
10. The crack-resistant concrete according to claim 7, characterized in that: The aspect ratio of the carbon fiber is 13-18:1; the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥20%.
Citation Information
Patent Citations
Concrete anti-cracking material as well as preparation method and application thereof
CN115745452A
Temperature-control phase-change release type hydration heat regulation and control material as well as preparation method and application thereof
CN116425452A
Concrete hydration temperature rise inhibitor as well as preparation method and application thereof
CN117326818A